Disparity between High Satisfaction and Severe Pain in Patients after Caesarean Section: A Prospective Observational-Controlled Investigation - Thomas Hesse; Andreas Julich; James Paul; Klaus Hahnenkamp; Taras I. Usichenko (Anesthesiology Research and Practice)
Objectives. Recent advances in the treatment of postoperative pain (POP) have increased the quality of life in surgical patients. The aim of this study was to examine the quality of POP management in patients after CS in comparison with patients after comparable surgical procedures. Methods. This was a prospective observational analysis in patients after CS in comparison with the patients of the same age, who underwent comparable abdominal gynaecological surgeries (GS group) at the university hospital. A standardised questionnaire including pain intensity on the Verbal Rating Scale (VRS-11), incidence of analgesia-related side effects, and incidence of pain interference with the items of quality of life and patients’ satisfaction with the treatment of POP was used. Results. Sixty-four patients after CS reported more pain on movement than the patients after GS (N=63): mean 6.1 versus 3.6 (VRS-11; P<0.001). The patients after CS reported less nausea (8 versus 41%) and vomiting (3 versus 21%; P<0.001) and demonstrated better satisfaction with POP treatment than the patients after GS: 1.4 (0.7) versus 1.7 (0.7) (mean (SD); VRS-5; P=0.02). Conclusion. The disparity between the high level of pain and excellent satisfaction with POP treatment raises the ethical and biomedical considerations of restrictive pharmacological therapy of post-CS pain.